Professional perspectives on digital transformation in heritage tourism site - Md Zain, Mazarina; Baniyamin, Nurhaya; Velusamy, Ramu; Yussof, Naeemah (Center of Research and Innovation Excellence (C-RIE) Politeknik Ungku Omar, 2025)
Augmented Reality (AR), Virtual Reality (VR) and Mixed Reality (MR) are promoting innovation and enhancing efficiency in multiple sectors. It helps to preserve cultural legacy for future generations. This study examines Malaysian heritage tourism professionals' views on the digital transformation of XR technology. The study questions professionals about Malaysia's heritage tourism industry's digital evolution. The goal is to learn about cultural heritage and architecture professionals' views on XR technology integration in heritage tourism. Semi-structured interviews and thematic analysis were used to identify themes and insights. Findings indicate that professionals strongly agree about the potential advantages of AR, VR and MR technologies in improving tourist engagement at cultural sites. The professionals value these technologies for their capacity to engage in urban landscapes through digital story design. However, significant issues include lack of experience, infrastructure, development expenses, and improper information display. To overcome these challenges, providing focused training, improving facilities, adopting efficient cost-control management, and fostering multidisciplinary collaboration is necessary. The need to form collaborative partnerships with higher education institutions and industry to reduce costs and access essential skills, ensuring that initiatives are highly competent and culturally authentic. Adopting XR technology is necessary for Malaysian cultural institutions.